Spark in the darkness: Discovering action potentials in brain tumors - Stevens, Nikolas; Drewa, Nina; Venkataramani, Varun (Cancer cell, 2024)
Gliomas exhibit significant molecular diversity and poor prognosis. In this issue of Cancer Cell, Curry et al. apply Patch-seq on human glioma samples uncovering hybrid cells with glial and neuronal features, capable of firing action potentials in isocitrate dehydrogenase mutant gliomas. These findings highlight the importance of neural features in tumor biology and progression.
Gesehen am 17.03.2025